Effects of AMF on Endogenous Hormones under Salt Stress in Roots of Phoebe Zhennan - Lingjun Cui, Kaiming Shi, (Design Engineering, 2020)
Under difference salt concentrations, the effects of Funneliformismosseae, an arbuscule mycorrhizal fungus (AMF), on the endogenous hormone contents in roots of Phoebe zhennan and their dynamic changes were investigated. The endogenous hormone contents were determined using an ELISA method. The contents of gibberellic acid (GA3), indole acetic acid (IAA), and zeatin nucleoside (ZR) in the roots of P. zhennan decreased with either the inoculation of AMF or non-AMF inoculation (NAMF) with the increase of salt concentration. The inoculation with AMF significantly reduced the endogenous hormone ratios in the roots. The ratios of ABA/GA3, ABA/IAA, ABA/ZR and ABA/(GA3+IAA+ZR) decreased by 18.55%, 28.13%, 89.91% and 24.74%, respectively, with AMF inoculation compared with that with NAMF inoculation at a salt concentration of 300mmol/L. Under salt stress at different salt concentrations, inoculation with AMF can alter the balance among endogenous hormones to increase the ABA content that promotes root growth and decreases the contents of GA3, IAA, and ZR that inhibit root growth.